2018
DOI: 10.1002/tsm2.61
|View full text |Cite
|
Sign up to set email alerts
|

Biplanar ultrasound investigation of in vivo Achilles tendon displacement non-uniformity

Abstract: The Achilles tendon is a common tendon for the medial and lateral gastrocnemius and soleus muscles. Non‐uniform Achilles tendon regional displacements have been observed in vivo which may result from non‐uniform muscle loading and intratendinous shearing. However, prior observations are limited to the sagittal plane. This study investigated Achilles tendon tissue displacement patterns during isometric plantarflexor contractions in the coronal and sagittal planes. Fourteen subjects (5 female, 9 male, 26 ± 3 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
0
23
1
Order By: Relevance
“…Non-uniform displacement within the Achilles tendon has been widely demonstrated under various static ( Arndt et al, 2012 ; Bogaerts et al, 2017 ; Stenroth et al, 2019 ) and dynamic ( Chernak Slane and Thelen, 2014 ; Franz et al, 2015 ; Franz and Thelen, 2015 ; Slane and Thelen, 2015 ) loading conditions. This non-uniformity decreases as people age ( Clark and Franz, 2020 ; Franz and Thelen, 2015 ; Slane and Thelen, 2015 ) and after repair of a ruptured tendon ( Beyer et al, 2018 ; Fröberg et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Non-uniform displacement within the Achilles tendon has been widely demonstrated under various static ( Arndt et al, 2012 ; Bogaerts et al, 2017 ; Stenroth et al, 2019 ) and dynamic ( Chernak Slane and Thelen, 2014 ; Franz et al, 2015 ; Franz and Thelen, 2015 ; Slane and Thelen, 2015 ) loading conditions. This non-uniformity decreases as people age ( Clark and Franz, 2020 ; Franz and Thelen, 2015 ; Slane and Thelen, 2015 ) and after repair of a ruptured tendon ( Beyer et al, 2018 ; Fröberg et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fascicles originating from different TS muscles exert differential forces and strains on each sub‐tendon 12,14 and are likely to cause non‐uniformities between fascicles arising from different muscle heads 12,14 . In several studies, the anterior (deep) tendon has been reported to displace more than the posterior (superficial) tendon 15‐18 . Furthermore, the different degrees of torsion among the population would lead to distinct non‐uniform displacement patterns within the AT for each group.…”
Section: Introductionmentioning
confidence: 99%
“…Individual control of sub-tendons creates non-uniform displacements within the Achilles tendon, and this non-uniformity has been observed in both passive [21-23] and dynamic [16, 24] movements. Furthermore, this displacement non-uniformity between the sub-tendons shows an age-related and disease-related decline [17, 25, 26].…”
Section: Introductionmentioning
confidence: 99%